Third Molar Impactions Prevalence and Pattern Among Adults Using 5923 Digital Orthopantomogram (Bangladesh Journal of Medical Science, 2022)
Background: Third molars positions and eruption patterns tend to be unpredictable in most cases. Substantial diversity exists globally among modern human races in the prevalence of third molar impaction.Aims and Method: This study aimed to investigate the prevalence and pattern of third molar impaction amongBangladeshi adults. Digital panoramic radiographs of 5923 patientswith the mean age of 35.90 ± 10.76 years olds were retrieved from database and evaluatedusingPlanmecaRomexis software.Demographics, gender and sidedifferences wereanalysed using SPSSversion 26.0.Result:Approximately, 46.2% of the adult population had third molar impaction where significant impaction occurred in the mandible compared to maxillary arch. However, no significant differences were observed among gender and side distribution. The most common type of third molar angulation in the maxilla and mandible was distoangular (55.9%) and mesioangular (36.6%), respectively.Comprehension of demographic and morphological variations in third molar impaction will lead to an understanding of third molar impaction assessment, which will aid in understanding the evolutionary origins of an important condition adversely affecting modern peoples.Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 717-729